CONTRIBUIÇÕES PARA O DEBATE SOBRE A ESCOLA PÚBLICA: O ÍNDICE DE DESENVOLVIMENTO DA EDUCAÇÃO BÁSICA (IDEB) - Fábio Mariano Da Paz (Universidade do Oeste Paulista, 2012)
This study presents some results obtained in the master research entitled "The Index of Basic Education Development (IDEB): a study of the city of Santa Fé do Sul / SP." It aims to address the operation of the Development Plan for Education (PDE) and its culmination in IDEB, globally analyzing its fundamentals, problems and prospects. It also aims, leaving data from desk research, interviews and questionnaires, reflect on the impact of rankings produced according to IDEB and practices increasingly currents of school accountability. To carry out the research in Santa Fe South had to elucidate mechanisms which triggered high IDEB increase in 2007 compared to 2005. The analyzes undertaken led to the finding of apparent failures in the consolidation of IDEB 2005 in the municipality of Santa Fe South, allowing infer that there was a great mistake in its disclosure by the MEC, by failing to recognize the weaknesses in data consolidation. Another interesting point concerns the confirmation of the existence of contradictory and unsustainable rankings IDEB, widely reported by the media.